Study of Subsidence detection by DinSAR and evaluation of some factors to the outcome - Anh, Tran Van; Cuong, Tran Quoc; Anh, Nguyen Duc; Khac, Dang Vu (Vietnam Journal of Earth Sciences, 2015)
The paper focuses on determining the subsidence by Differential Interferometric Synthetic Aperture Radar (DInSAR) using two methods (Two-pass and Three-pass) and assessing the effect of some error sources to the results. Errors effecting the result include atmospheric, phase due to signal-to-noise ratios, number of looks, pixel misregistration and baseline decorrelation; however, especially significant is  (Digital Elevation Model) DEM error. We proved that application of DEM with low precision would create virtual subsidence. The experiment area is Hanoi city, data was Envisat ASAR image, C band with the wavelength of 5.6cm. By using SARscape software for processing, with Two-pass method a virtual subsidence was found at one site in northern part of Hanoi near the Red River (Song Hong).  With the Three-pass method this subsidence site did not occurred. Besides,  results of surface subsidence detection using DInSAR methods were compared with those measured directly from monitoring stations located close to water supplying wells. As a result, data acquired from  Ha Dinh and Thanh Cong stations were closely distributedto those determined by DInSAR method. Unfortunately, the subsidence data acquired by direct measurement had been conducted continuously only from 2000 to 2003 instead to 2005; whereas the Envisat ASAR subsidence data are available only from 2003 to 2004.  Therefore, combination of data of direct measurement at Ha Dinh and Thanh Cong stations, and DInSAR processing should provide a linear correlation. . The study proves using DInSAR with Three-pass method would provide more reliable result as compared to the Two-pass method even with a limited amount of images.References Colesanti, C., Ferretti, A., Novali, F., Prati, C. and Rocca, F., 2003: SAR monitoring of progressive and seasonal ground Deformation using the permanent scatterers technique, IEEE Transaction on Geoscience and Remote Sensing, 41, 1685-1701. Dehls, J.F., Basilico, M. and Colesanti, C., 2002: Ground deformation monitoring in the Ranafjord area of Norway by means of the permanent scatterers technique, 23th International Geoscience and Remote Sensing Symposium (Expanded Abstract), Toronto, June 24-28, p. 203-207. Ferretti, A., Prati, C. and Rocca, F., 2000: Nonlinear subsidence rate estimation using permanent scatterers in differential SAR interferometry, IEEE Transaction on Geoscience and Remote Sensing, 38, 2202-2212. Gabriel, A.K., Goldstein, R.M. and Zebker, H. A., 1989: Mapping small elevation changes over large areas: Differential Radar Interferometry, Journal of Geophysical Research, 94 (B7), pp. 9183-9191. Goldstein, R. M., Engelhardt, H., Kamb, B. and Frolich, R.M., 1993: Satellite radar interferometry for monitoring ice sheet motion: Application to an Antarctic icestream.Science, 262, pp. 1525-1530. Graham, L.C., 1974: Synthetic Interferometer Radar for Topographic Mapping, Proceedings of the IEEE, 62(6), pp. 763-768. Gray, A.L., Mattar, K.E. and Sofko, G., 2000: Influence of ionosphereic electron density fluctuations on satellite radar interferometry, Geophysical Research Letters, 27(10), pp. 1451-1454. Hanssen, R.F. and Feijt, A., 1996: A first Quantitative Evaluation of Atmospheric Effects on SAR Interferometry, Proceedings of the ‘Fringe 96’ Workshop on ERS SAR Interferometry, Zurich, Switzerland, pp. 277-282. Hooper, A., Segall, P., and Zebker, H., 2007: Persistent scatterer interferometric synthetic aperture radar for crustal deformation analysis, with application to Volcan Alcedo, Galapagos, Journal of Geophysical Research, 112, 7, B07407, doi:10.1029/2006JB004763. K. V. Dang, C. Doubre, C. Weber, F. Masson, and N. Gourmelen, 2013: Recent land subsidence caused by the rapid urban development in the Hanoi urban region (Vietnam) using ALOS. InSAR data, journal Natural Hazards and Earth System Sciences (NHESS). Kampes B. and Usai S., The Delft Object-oriented Radar Interferometric software, Proc. 2nd Int. Symp.Operational Rem. Sensing, ITC, Enschede, The Netherlands, 16th August 1999., 4 pages (CD-ROM). Massonnet, D., Rossi, M., Carmona, C., Adragna, F., Peltzer, G., Feigi, K. and Rabaute, T., 1993: The displacement field of the Landers earthquake mapped by radar interferometry, Nature, 364, pp.138-142. Massonnet, D. and Feigl, K.L., 1998: Radar interferometry and its application to changes in the earth’s surface, Reviews of Geophysics, 36(4), pp.441-500. Nhan Pham Quy, et al., 2008: Research and assessment potential ground water resource of Hanoi area, degeneration groundwater reserve and quality, built-up orientation strategy for reasonable exploitation water, protection environment for sustainable development capital. Final Report. Hanoi research project code: 010-04/09-2008-2. Price, E. J and Sandwell, D. T., 1998: Phase gradient approach to stacking interferograms,Journal of Geophysical Research, 103(B12), pp. 30183-30204. Rott, H., Mayer, C. and Siegel, A., 2000: On the operational potential of SAR interferometry for monitoring mass movements in Alpine areas,Proceedings of EUSAR2000, Munich, Germany, pp.43-46. Sowter, A. & Warren, M., 2005: Reducing the DEM Error Effect in Differential Interferometry, Fringe 2005 Workshop, Proceedings of the Conference. Tran Van Anh, Shinji Masumoto, KiyojiShiono and VenkateshRaghavan, 2007: Spatial distribution of subsidence in Hanoi detected by JERS-1 SAR interferometry, Journal of GeoInformatics-Japan, Vol. 18, no.1. Wegmüller, U., Werner, C., Wiesmann, A. and Strozzi, T., 2003: Interferometricpoint target analysis with JERS-1 L-band SAR data, IGARSS'03, Toulouse, France. Zebker, H.A. and Goldstein, R.M., 1986: Topographic mapping from interferometricsynthetic aperture radar observations, Journal of Geophysical Research, 91(B5), pp. 4993-4999. Zebker, H. A. and Villasenor, J., 1992: Decorrelation in interferometric radar echoes,IEEE Transactions on Geoscience and Remote Sensing, 139(2), pp. 88-97. Zebker, H. A., Rosen, P. A., Goldstein, R. M., Gabriel, A. and Werner, C. L., 1994: On the derivation of coseismic displacement fields using differential radar interferometry: The Landers earthquake, Journal of Geophysical Research, 99(B), pp.1961-1967. Zebker, H.A., Rosen, P.A. and Hensley, S., 1997: Atmospheric effects ininterferometricsynthetic aperture radar surface deformation and topographic maps, Journal of Geophysical Research, 102(B4), pp.7547-7563.